The role of electronic promotion tools in achieving customer satisfaction A (field) study on MTN customers on the Syrian coast (Latakia University Journal - Economic and Legal Sciences Series, 2024)
The great development in information and communication technology prompted businessorganizations to introduce modern technologies into their business and use them as a tool to promote their products. Among the methods of modern technologies that were used was electronic promotion. Today, electronic promotion is a means that can deliver the promotional message to the customer at any time and place. Therefore, any organization that seeks to reach the largest possible number of customers and gain their satisfaction needs to adopt electronic promotion. MTN was among the companies that adopted the concept of e-promotion. Proceeding from that, the aim of this research is to determine the role played by electronic promotion tools in affecting customer satisfaction in the MTN telecommunications company, where 410 questionnaires were distributed to the company's customers, 400 questionnaires were retrieved, 390 of which could be analyzed. One of the most important findings of the research is that the electronic promotion tools used by MTN affect the satisfaction of its customers. And that the company's e-mail had a weak effect on the satisfaction of its customers, as the e-mail is used by the company's customers only in a small way as a result of its lack of effectiveness, and this is evidence of not using it and dealing with it properly and in a manner commensurate with the needs and desires of customers and achieve their satisfaction.